VIRTUAL REALITY ENVIRONMENT TRAINING EFFECT ON DYNAMIC AND STATIC STABILITY AMONG ATHLETES FROM RANDOM INTERMITTENT DYNAMIC TYPE SPORTS - Mohammad Ahsan; Qassim Ibrahim Muaidi; Turki Saeed Abualait (Journal of Physical Education, 2022)
ABSTRACT This study aims to investigate the aftereffect of a six-week virtual reality environment training on dynamic and static postural stability in athletes participating in random intermittent dynamic type sports. The pretest and posttest study designs were chosen to conduct this study. Twenty-four male athletes were selected for the study. Participants participated in a six-week virtual reality environment training program three times a week for a session of forty-five minutes. The virtual reality environment was created using CAREN's integrated virtual reality system with Motek's D-flow application. The postural stability was assessed using a stadiometer. Assessments were performed before and after six weeks of training. A paired sample t-test was used to determine differences between pretest and posttest outcome measures. The improvement can be seen as an effect of virtual reality environment training intervention. Statistically significant differences were observed between pretest and posttest for dynamic and static anteroposterior and mediolateral postural stability at 20 and 40 levels of difficulty. The virtual reality environment training helps to improve performance by assessing and optimizing the training load in the process of improving the performance of athletes participating in random intermittent dynamic type sports.